Investment support of the state information security of Ukraine in the conditions of martial law: the analysis of actual legislative innovations - Shevchuk, Oksana; Mentukh, Natalia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2022)
This scientific article highlights the issue of ensuring the investment component of information security of the state in martial law.Theoretical and practical interest in the study of the problems of legal security of military security is primarily related to the social, economic and geopolitical metamorphoses that have taken place in the world in recent years. In the current realities of Ukraine, it faces a number of issues, the solution of which is directly related to the identification and analysis of sources of real and potential threats to national interests. A significant number of global threats require the creation of special administrative and legal mechanisms for regulating public relations that arise in emergencies of military, social, man-made and natural nature.The purpose of this article is to study some forms of investment support for state information security of Ukraine in martial law.The authors conclude that the business has continued to pay taxes to the state budget and even pays them in advance. In February 2022, the general fund of the state budget received UAH 104.6 billion (overfulfillment of the monthly schedule by 29.3%, or UAH 23.7 billion). With the planned deficit of UAH 66.2 billion in the first two months of 2022, the general fund surplus amounted to UAH 13.1 billion, and the state budget of Ukraine as a whole - UAH 24 billion;The NBU promptly transferred part of the profits for distribution in the amount of almost UAH 19 billion to the state budget of Ukraine to finance the functioning of the state under martial law;International organizations and partner countries have pledged large amounts of funding to strengthen defense capabilities, support Ukraine's economy and humanitarian issues. According to the NBU, the total international financial, technical and humanitarian support is more than $ 15 billion, of which more than $ 5 billion - immediately to the budget.